Hydrogen production from steam gasification of tableted biomass in molten eutectic carbonates. (30th August 2019) - Jin, Ke; Ji, Dengxiang; Xie, Qinglong; Nie, Yong; Yu, Fengwen; Ji, Jianbing
Abstract: The steam gasification of tableted biomass for H2 production in molten salts was investigated under different conditions. The results showed that the ternary molten carbonates (32 wt% Li2 CO3, 33 wt% Na2 CO3 and 35 wt% K2 CO3 ) acted as heat medium and catalyst in the gasification process. The use of molten salts could significantly increase total gas and H2 production and simultaneously decrease the concentrations of CO and CH4 in the product gas, and also decrease the yield of condensable tar. The increase in gasification temperature and mass ratio of steam to biomass (S/B) was beneficial for H2 production process. However, excessive steam contributed slightly to the increase in H2 production and largely increased the energy consumption. The optimal S/B ratio was found to be 1.0. The feedstock after tabletting could completely immersed in molten salts, which improved the contact between biomass and molten salts and thus favored the biomass gasification for H2 production. When biomass particle size was 0.25 g/piece, the yield of H2 reached 807.53 mL/g biomass. Graphical abstract: Image 1 Highlights: Steam gasification of biomass in molten salts was performed. Molten salts possess effects like catalysis and heat transfer during gasification. Molten salts increased H2 content and yield by 16.92 vol% and 311.50 mL/g biomass. Increase in temperature and S/B ratio was beneficial for H2 production. Contact between feedstock and molten salts was favored by tabletting of feedstock.